Total synthesis of (+)-petromyroxol via tandem alpha-aminoxylation-allylation and asymmetric dihydroxylation-S(N)2 cyclization approach - Nookaraju, U.; Kumar, Pradeep (RSC Advances, 2015)
The total synthesis of (+)-petromyroxol, a tetrahydrofuran (THF)-diol fatty acid, isolated from sea lamprey larvae (Petromyzon marinus) is reported. The present synthesis employs a tandem alpha-aminoxylationallylation, cross metathesis and tandem asymmetric dihydroxylation-S(N)2 cyclization as key steps.